2023
DOI: 10.3389/fbioe.2023.1293705
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of tendon strains in jersey finger injury load cases using a finite element neuromuscular human body model

Lennart V. Nölle,
Eduardo Herrera Alfaro,
Oleksandr V. Martynenko
et al.

Abstract: Introduction: A common hand injury in American football, rugby and basketball is the so-called jersey finger injury (JFI), in which an eccentric overextension of the distal interphalangeal joint leads to an avulsion of the connected musculus flexor digitorum profundus (FDP) tendon. In the field of automotive safety assessment, finite element (FE) neuromuscular human body models (NHBMs) have been validated and are employed to evaluate different injury types related to car crash scenarios. The goal of this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…Simulating injury using digital HBM's is complex because of the wide variety of factors that can affect the calculated risk of injury. During a vehicle collision [75], athletic injury [6], [7], or in response to vibration [5], the body's musculature may have time to activate, alter the movements of the body, and change the risk of injury. In this work, we have evaluated the accuracy of three different muscle models in LS-DYNA by simulating laboratory experiments that examine the force-length-velocity relations during maximal and submaximal activation, the response of muscle to active-lengthening, and the frequency-response of muscle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Simulating injury using digital HBM's is complex because of the wide variety of factors that can affect the calculated risk of injury. During a vehicle collision [75], athletic injury [6], [7], or in response to vibration [5], the body's musculature may have time to activate, alter the movements of the body, and change the risk of injury. In this work, we have evaluated the accuracy of three different muscle models in LS-DYNA by simulating laboratory experiments that examine the force-length-velocity relations during maximal and submaximal activation, the response of muscle to active-lengthening, and the frequency-response of muscle.…”
Section: Discussionmentioning
confidence: 99%
“…Digital human body models (HBM) are used to evaluate the risk of injury during low-velocity vehicle collisions [1], [2], from exposure to vibration [3]- [5], and as a result of athletic accidents [6], [7]. Simulating injury-causing scenarios is challenging because the musculature of the body may have time to activate [8], altering the ensuing movement [9], [10], and affect the risk of some types of injury.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, they can be easily applied to any muscle, with their inherent scalability eliminating the chance of a mismatch between the muscle material parameters and the defined injury thresholds. In contrast, only one fixed set of strain based TSIC injury thresholds has been proposed thus far [43]. This limits the applicability of the criterion to a subset of tendons which exactly match the deformation characteristics of the stress-strain curve used to define the TSIC threshold values.…”
Section: Methodsmentioning
confidence: 99%
“…The assessment of muscle and tendon strain injury severity was performed using two injury criteria, the MSIC [42] and the TSIC [43]. Both criteria categorise the grade of the sustained strain injury based on the deformation stages of the muscle and tendon (Fig 3) as previous studies [63][64][65][66] have shown that the regions of the stress-strain curve can be linked to the degree of tissue damage.…”
Section: Applied Injury Criteriamentioning
confidence: 99%
See 1 more Smart Citation